Revalidation and adaptation of the Menstrual Practice Needs Scale (MPNS) in a cross-sectional survey to measure the menstrual experiences of adult women working in Mukono District, Uganda. Issue 7 (1st July 2022) - Hennegan, Julie; Bukenya, Justine N; Kibira, Simon P S; Nakamya, Petranilla; Makumbi, Fredrick E; Exum, Natalie G; Schwab, Kellogg J
Abstract : Objectives: The Menstrual Practice Needs Scale (MPNS) is a comprehensive measure of menstrual self-care experience including access to sufficient, comfortable materials to catch or absorb bleeding, supportive spaces for managing menstruation and for disposal and laundering of used materials. It addresses a critical measurement gap to improve quantitative menstrual health research and programme evaluation. The scale was validated in a population of adolescent schoolgirls. This study appraises its performance among adult women. Design: Cross-sectional survey. Setting and participants: Seven cognitive interviews provided insights into the interpretability of scale items. A survey of 525 working women who had menstruated in the past 6 months (435 working in markets, 45 in schools and 45 working in healthcare facilities) in Mukono District, Uganda was used to test the dimensionality, reliability and validity of the measure. Results: The 36 scale items were well understood by the study population. Dimensionality was tested for the 28 items relevant to women disposing of menstrual materials and 32 items relevant to those washing and reusing materials. The original subscale structure fit with the data, however, fell short of recommended thresholds for those disposing of materials (root mean squared error of approximation, RMSEA=0.069; Comparative Fit Index, CFI=0.840; Trucker-Lewis Index, TLI=0.824). An alternative subscale structure was an acceptable fit for those disposing (RMSEA=0.051; CFI=0.911; TLI=0.897) and reusing materials (RMSEA=0.053; CFI=0.915; TLI=0.904). MPNS total and subscale scores demonstrated acceptable internal consistency. Higher scores reflected more positive menstrual experiences and were associated with well-being (total score r=0.24, p<0.001), not missing work due to the last menstrual period (total score OR=2.47 95% CI 1.42 to 4.30) and confidence to manage menstruation. Conclusions: The MPNS offers a valid and reliable way to assess menstrual health needs. The revised factor structure can be used for samples of adult workers. Findings also highlight challenges in assessing the variety of experiences relevant to managing menstrual bleeding.